Pernicious anemia and gastric athropy - Mechán, Victor (2012)
We present the case of an 84-year old male farmer, who was diagnosed in 2001 with megaloblastic anemia associated to vitamin B12 deficiency, sensory-motor polyneuropathy in his lower limbs and gastric atrophy with intestinal metaplasia. The patient was treated with a combination including 1000 mcg folic acid and 8 mcg cyanocobalamin. He improved his hemoglobin levels back to normal after 2 months of therapy. One year later, he stooped therapy because he was feeling better. In 2008, anemia and the sensorial motor polyneuropathy reappeared, together with an inadequate perception of normal flavor. At this time studies showed the following: pancytopenia, severe megaloblastic anemia, vitamin B12 deficiency, gastric atrophy, gastric polyps and xanthomas, intestinal metaplasia, serum lipid abnormalities, facial xerosis and generalized white spotted macular lesions (2-3 mm). He was treated with parenteral cyanocobalamin, and the patient now still has gastric atrophy, although the sensorial-motor polyneuropathy had disappeared and his hemoglobin levels are once again normal.